Practical design optimization of cellular structures for additive manufacturing. Issue 11 (1st November 2020) - Wang, Yu; Hu, Dezheng; Wang, Hailin; Zhang, Tinghao; Yan, Hao
Abstract : This article proposes a practical technique for designing cellular structures with the configuration of spatially varying structures of unit cells for additive manufacturing processes. At the macroscale, global structures are optimized based on an element-wise topology optimization method to generate an overall layout involving solid, void and lattice materials. At the mesoscale, the effective properties of planar unit cells with graded geometric feature parameters are evaluated via a numerical homogenization method. Communication between unit cells and global structures is established based on a set of property-fitting functions to approximate intermediate element properties. To enhance the manufacturing of the resulting designs, the minimum feature size is constrained and an additional solid layer is attached to the structural boundaries. The design of a cantilever beam is presented to demonstrate the effectiveness of the proposed technique. The effects on mechanical performance of lattice materials with different topologies are numerically analysed and experimentally validated.